Comparison of Antioxidant Activity of Roccella phycopsis Ach. (Roccellaceae) and Flavoparmelia caperata L. Hale (Parmeliaceae) Lichens - Sinem Aydın; Kadir Kınalıoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The antioxidant activity of Roccella phycopsis Ach. and Flavoparmelia caperata L. Hale lichens was determined by their ability to scavenge free radicals like DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2’-azinobis-(3-ethylbenzothiaziline-6-sulfonate). Total phenolic and flavonoid contents, metal chelating activity and reducing power of the extracs were also measured. Both lichens species displayed noticeable antioxidant activity. The total flavonoid content of methanol and ethanol extracts of the lichens ranged from 110.06±0.004 µg/mL to 154.1±0.007 µg/mL and from 40.96±0.005 µg/mL to 65.23±0.007 µg/mL, respectively. F. caperata lichen showed higher ferric reducing antioxidant power and DPPH radical quenching activity than R. phycopsis lichen. Based on the obtained results, this lichen species are natural sources of antioxidant substances.